2010
DOI: 10.1016/j.jeem.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Building out alternative fuel retail infrastructure: Government fleet spillovers in E85

Abstract: One significant obstacle to meeting aggressive federal and state alternative fuel consumption targets is the relative scarcity of retail fueling stations that carry alternative fuels. Policies that encourage or mandate use of alternative fuel vehicles in government fleets, thereby increasing demand for such fuels, are one popular approach to stimulating further development of the alternative fuel retail infrastructure. I focus specifically on flex-fuel vehicles (FFVs) that burn E85, a combination of 85% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…Our work contributes first to the literature studying market impacts of the RFS. Previous work has estimated demand for E85 and the role of policy in driving diffusion new alternative fuels (Corts, 2010;Anderson, 2012;Langer and McRae, 2014;Pouliot and Babcock, 2017). More recent empirical work has studied RIN cost drivers, as well as the effect of RIN prices on refiners' markups and profitability (Lade et al, 2016;Burkhardt, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our work contributes first to the literature studying market impacts of the RFS. Previous work has estimated demand for E85 and the role of policy in driving diffusion new alternative fuels (Corts, 2010;Anderson, 2012;Langer and McRae, 2014;Pouliot and Babcock, 2017). More recent empirical work has studied RIN cost drivers, as well as the effect of RIN prices on refiners' markups and profitability (Lade et al, 2016;Burkhardt, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the suboptimal placement of some federal FFVs, the fact remains that EPAct 1992 has been successful at getting FFVs deployed throughout the federal fleet: 63% of the 174,469 federal FFVs were determined to have access to alternative fuel during FY 2012, a significant improvement from FY 2009, when only 54% had access. 4 Another noteworthy success comes from Corts (2010), who found that mandated government AFV acquisition programs in effect provide an incentive for retail station owners to invest in alternative fuel. He further concluded that "…a government fleet mandate is essentially a costless initiative that apparently yields sizable benefits in terms of stimulating E85 availability" (p.232), whereas the impact of private FFV ownership was much less important to stimulating E85 infrastructure development.…”
Section: Energy Policy Program Evaluationmentioning
confidence: 99%
“…After 2011, policy decisions aimed at stabilizing inflation have strongly contributed to the loss of competitiveness of ethanol [18]. Some studies evaluates the hydrous ethanol as automotive fuel and its relation to the gasoline market regarding the issue of expanding the distribution network in US [19][20][21]. On the other hand, Brazil has a mature ethanol retail market, established since Pro-Álcool.…”
Section: Introductionmentioning
confidence: 99%